2011
DOI: 10.1142/s1363919611003258
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Business Performance in Small Enterprises: An Enterprise-Level Analysis

Abstract: This paper explores links between developed innovations and business performance in small enterprises with fewer than 50 employees. It also examines how performance has changed over time during a period of five years. The empirical evidence is based on two quantitative datasets describing innovation and business performance in 145 small enterprises in 2005–2009. The study makes a contribution to academic literature by providing a detailed view of the differences in performance across innovation types. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 33 publications
2
39
0
4
Order By: Relevance
“…Firstly, authors argue that innovative behaviour leads to improved operational performance such as cost efficiency, quality improvement and speed to market, which ultimately results in higher profitability and sales growth (Cambra-Fierro et al 2011;Ul Hassan et al 2013). Secondly, authors (Basterretxea & Martinez 2012;Cortez & Cudia 2010;Forsman & Temel 2011) argue that both profitability and sales growth are the most common indicators used in prior studies to measure organisational performance and, as such, enable a comparison between the output of prior studies and the study in question.…”
Section: Financial Measuresmentioning
confidence: 99%
“…Firstly, authors argue that innovative behaviour leads to improved operational performance such as cost efficiency, quality improvement and speed to market, which ultimately results in higher profitability and sales growth (Cambra-Fierro et al 2011;Ul Hassan et al 2013). Secondly, authors (Basterretxea & Martinez 2012;Cortez & Cudia 2010;Forsman & Temel 2011) argue that both profitability and sales growth are the most common indicators used in prior studies to measure organisational performance and, as such, enable a comparison between the output of prior studies and the study in question.…”
Section: Financial Measuresmentioning
confidence: 99%
“…Keizer et al [49] emphasize that the firm's innovation performance depends on the opportunities provided by their external environment. SMEs in Dubai can use innovation as a tool to achieve better business performance [6] , having in mind that important innovations are those that contribute to business performance [25] . Some studies have found a significant relationship between innovation and sales growth and profitability [50] while others have found a non-significant relationship between innovation and return on investment [6] , but the link between innovation and business performance needs to be tested in a different market context [51] .…”
Section: Innovation and Business Performancementioning
confidence: 99%
“…An increasing number of studies have explored the impact of strategic orientations (for example technology orientation) on innovation and business performance [4,5] . Previous studies have focused on Western markets and have yielded mixed results, some positive, some negative and some have found no evidence of an impact [5,6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…The negative correlation and beta imply that the existence of technology-related problems has the effect of reducing the performance of businesses in the food processing industry. In support, the results of studies conducted by Tavitiyaman, Zhang andQu (2011) andForsman andTemel (2011) showed a strong negative relationship occurring between technology-related problems and business performance. These results were connected to the decrease in both market share and profits by businesses experiencing technology-related problems, as they were unable to match the performance of their technologically advanced competitors.…”
Section: Technology and Business Performancementioning
confidence: 70%